MISOGYNY PADA REFERENSI TERHADAP ISTRI DALAM BAHASA KOREA - Inggrid Prinsia Maharani (Balai Bahasa Provinsi Riau, 2023)
South Korea, one of the most advanced countries in terms of civilization and technology, is not immune from issues of misogyny or hatred towards women. This phenomenon can be said to still be attached to culture and become a legacy until this day. Women are still required to follow the gender roles determined by society, namely as wives who take care of the household. This can be seen from the use of reference words for wife in Korean, where many of them have derogative meanings and history towards women. This study then analyzes these words historically and relates them to the current situation. The problem that arises is that most of these terms are still used in society, where awareness of gender equality should now be a matter of concern.